2013
DOI: 10.1074/jbc.m113.521815
|View full text |Cite
|
Sign up to set email alerts
|

Plant Acyl-CoA:Lysophosphatidylcholine Acyltransferases (LPCATs) Have Different Specificities in Their Forward and Reverse Reactions

Abstract: Background: Acyl-CoA:lysophosphatidylcholine acyltransferase (LPCAT) enzymes have central roles in acyl editing of phosphatidylcholine.Results: Plant LPCATs were expressed in yeast and biochemically characterized.Conclusion: LPCATs can edit acyl composition of phosphatidylcholine through their combined forward and reverse reactions.Significance: Plant LPCATs play a role in editing both sn-positions of PC and remove ricinoleic acid with high selectivity from this lipid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
174
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(186 citation statements)
references
References 44 publications
11
174
1
Order By: Relevance
“…Taken together with earlier reported in vitro data on plant LPCAT action (13), our data further confirm that plant LPCAT can act in a reversible fashion under in vivo condition. These data demonstrate for the first time in vivo evidence of the reversibility of the LPCAT.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Taken together with earlier reported in vitro data on plant LPCAT action (13), our data further confirm that plant LPCAT can act in a reversible fashion under in vivo condition. These data demonstrate for the first time in vivo evidence of the reversibility of the LPCAT.…”
supporting
confidence: 78%
“…Recently, by using reverse genetics and metabolic labeling approaches, it was demonstrated that LPCAT-mediated acyl-editing together with phosphatidylcholine:diacylglycerol cholinephosphotransferase-based PC-sn-1,2-diacylglycerol interconversion control the major fluxes of PUFAs from PC to TAG (ϳ66%) in Arabidopsis seeds (12). In addition, in vitro evidence has shown that plant LPCAT does indeed operate in a reversible fashion, even though the reverse reaction is a thermodynamically unfavorable process (13). Despite recent progress, direct evidence of how LPCAT interacts with the enzymes involved in the Kennedy pathway is still lacking.…”
mentioning
confidence: 99%
“…3A). However, this loss of oleate from PC through the preferential hydrolysis of 18:1-PC over sn-1-palmitoylsn-2-ricinoleoylphosphatidylcholine (Ric-PC) may be mitigated to some extent through the selective reacylation of LPC by the endogenous Arabidopsis LPCATs (Lager et al, 2013). The newly liberated oleic acid would have to be reactivated to its CoA-thioester, prior to transfer catalyzed by LPCAT into PC, via the catalytic action of long-chain acyl-coenzyme A synthetase (LACS; Shockey et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Lands (1960), PC deacylation was initially thought to result from the activity of a phospholipase. Until now, in plants, however, evidence suggested that LPC production comes from the action of phospholipid:diacylglycerol acyltransferase (PDAT; Zhang et al, 2009;van Erp et al, 2011;Xu et al, 2012) and through the reverse activity of LPCAT (Stymne and Stobart, 1984;Yurchenko et al, 2009;Lager et al, 2013). Thus, acyl editing includes a broader set of enzymatic activities than originally envisioned by Lands (1960).…”
mentioning
confidence: 93%
“…Acyl groups esterified to PC become substrates for FA desaturation and other modifications (Miquel and Browse, 1992;Broun et al, 1998) and can then be returned back to the acyl-CoA pool or channeled into TAG through acylCoA-independent mechanisms (Stymne and Stobart, 1984;Weselake, 2005;Lager et al, 2013). The efficiency of this acyl group channeling to and from PC is an important determinant of the overall composition of FAs in the acyl-CoA pool and, subsequently, in seed oil.…”
mentioning
confidence: 99%